Lottery, luck, or legacy. A review of "The Genetic Lottery: Why DNA matters for social equality". (1st April 2022) - Coop, Graham; Przeworski, Molly
Abstract: A book review of " The genetic lottery: why DNA matters for social equality ." (Princeton University Press, 2021) by Kathryn Paige Harden.